Gastrointestinal disorders in Curry–Jones syndrome: Clinical and molecular insights from an affected newborn. Issue 6 (6th April 2017) - Wigby, Kristen; Twigg, Stephen R. F.; Broderick, Ryan; Davenport, Katherine P.; Wilkie, Andrew O. M.; Bickler, Stephen W.; Jones, Marilyn C.
Abstract : Curry–Jones syndrome (CJS) is a pattern of malformation that includes craniosynostosis, pre‐axial polysyndactyly, agenesis of the corpus callosum, cutaneous and gastrointestinal abnormalities. A recurrent, mosaic mutation of SMO (c.1234 C>T; p.Leu412Phe) causes CJS. This report describes the gastrointestinal and surgical findings in a baby with CJS who presented with abdominal obstruction and reviews the spectrum of gastrointestinal malformations in this rare disorder. A 41‐week, 4, 165 g, female presented with craniosynostosis, pre‐axial polysyndactyly, and cutaneous findings consistent with a clinical diagnosis of CJS. The infant developed abdominal distension beginning on the second day of life. Surgical exploration revealed an intestinal malrotation for which she underwent a Ladd procedure. Multiple small nodules were found on the surface of the small and large bowel in addition to an apparent intestinal duplication that seemed to originate posterior to the pancreas. Histopathology of serosal nodules revealed bundles of smooth muscle with associated ganglion cells. Molecular analysis demonstrated the SMO c.1234 C>T mutation in varying amounts in affected skin (up to 35%) and intestinal hamartoma (26%). Gastrointestinal features including structural malformations, motility disorders, and upper GI bleeding are major causes of morbidity in CJS. Smooth muscle hamartomas are a recognized feature of children with CJS typically presenting with abdominal obstruction requiring surgical intervention. A somatic mutation in SMO likely accounts for the structural malformations and predisposition to form bowel hamartomas and myofibromas. The mutation burden in the involved tissues likely accounts for the variable manifestations.